2002
DOI: 10.1007/s00204-002-0346-6
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin and fisetin induction of apoptosis through activation of caspase 3 cascade and alternative expression of p21 protein in hepatocellular carcinoma cells SK-HEP-1

Abstract: Wogonin and fisetin are flavonoids, which are widely distributed in plants. Our recent study demonstrated that, among seven structurally related flavonoids, wogonin and fisetin showed the most potent apoptosis-inducing activities in human promyeloleukemic cells HL-60. In the present investigation, we performed molecular studies to assess the apoptotic effects of wogonin and fisetin on hepatocellular carcinoma cells SK-HEP-1. Both wogonin and fisetin showed dose-dependent cytotoxic effects on SK-HEP-1 cells, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
109
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(120 citation statements)
references
References 28 publications
7
109
0
4
Order By: Relevance
“…Flavonoids have been shown to alter a number of key proteins implicated in growth and differentiation. These include induction of cyclin-dependent kinase (cdk) inhibitors p21 Cip1/WAF1 and p27 Kip1 , 39,42 inhibition of phosphorylation of retinoblastoma (Rb) protein, 43 decrease in levels of cyclins B, D and E and cdk 2,4 and 6, 44-46 induction of apoptosis, 47,48 inhibition of topoisomerase II, and alterations to the MAPkinase pathway. 49 Genestein, a soy isoflavone, enhances the antiproliferative effects of vitamin D by upregulating vitamin D receptor and p21 Cip1/WAF1 protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids have been shown to alter a number of key proteins implicated in growth and differentiation. These include induction of cyclin-dependent kinase (cdk) inhibitors p21 Cip1/WAF1 and p27 Kip1 , 39,42 inhibition of phosphorylation of retinoblastoma (Rb) protein, 43 decrease in levels of cyclins B, D and E and cdk 2,4 and 6, 44-46 induction of apoptosis, 47,48 inhibition of topoisomerase II, and alterations to the MAPkinase pathway. 49 Genestein, a soy isoflavone, enhances the antiproliferative effects of vitamin D by upregulating vitamin D receptor and p21 Cip1/WAF1 protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effects of baicalein and baicalin on expansion of human viruses (Bayer et al, 1992;Wu et al, 1995), and a protective effect of baicalin on renal cell injury (Yokozawa et al, 1999) have been reported. It was also reported that baicalein, baicalin and wogonin showed suppression activity against the production of nitric oxide/prostaglandin E 2 (Chen et al, 2001;Chi et al, 2001) and proliferation of cancer cells (Chan et al, 2000;Chen et al, 2002;Matsuzaki et al, 1996;Okita et al, 1993;Yano et al, 1994).…”
Section: Introductionmentioning
confidence: 97%
“…At present, fisetin has shown multiple biological activities including anti-proliferative (7,8), pro-apoptotic (9-13), neuroprotective (14) and anti-oxidative activities (15). Moreover, fisetin has been shown to suppress the proliferation of a wide variety of tumor cell, including prostate cancer (16), liver cancer (17), colon cancer (18) and leukemia (19) cells, and inhibit the mitogen-activated protein kinase (MAPK) and nuclear factor (NF)-κB signaling pathways in various type of cancer cell, such as colon and pancreatic cancer (14,(20)(21)(22)(23)(24). Fisetin was also reported to reduce the invasive and migratory capacity of the A549 human lung cancer cell line via the extracellular signal-regulated kinase (ERK) signaling pathway (25).…”
Section: Introductionmentioning
confidence: 99%